Community forestry: A social alliance - Macqueen, Duncan; Grouwels, Sophie (Technical Centre for Agricultural and Rural Cooperation, 2011)
Forest Connect works in 12 countries to link small-scale forestry enterprises to each other and to national institutions, and helps them to gather and deliver information using ICTs.